Indian Stock Market Growth VS Global Uncertainty: An Empirical Analysis (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The Indian stock market has demonstrated strong resilience despite ongoing global economic uncertainty caused by geopolitical conflicts, inflationary pressures, and monetary tightening. This study examines the relationship between Indian stock market performance and global uncertainty during the period 2024–2026. Using secondary data from government reports, financial publications, and academic literature, the study evaluates the role of domestic macroeconomic factors, foreign institutional investment flows, and policy stability. The findings indicate that while global uncertainty affects short-term volatility, India’s strong domestic demand, robust institutional framework, and increasing participation of domestic investors contribute to sustained long-term growth. The study concludes that India is gradually achieving partial decoupling from global financial shocks.